De volta ao lugar de aluna: as relações docência-discência na formação de professoras - Simone Medeiros de Carvalho (2012)
Historically, the teacher's formation walked into the institutionalization with the creation of the Normal Schools in the 19th century, the institution of the Pedagogy courses in the beginning of the 20th century and the educational reforms of the 1990 decade that created the Superior Institutes of Education and the Normal Superior course. These spaces and models for the teaching formation were supplanted in the Curricular Guidelines of the Pedagogy course in 2006 that gave to elementary school teacher´s the universitary status through the Pedagogy course. Today, all the students of the Pedagogy course are candidates to the spots of elementary school teacher´s. Currently, there is no distinction between the student that already have the graduation in high school [or not] of the professorship course, the student that already clerks the teacher´s career, and the student that never had formal contact [as a teacher] with the career. So, coexists, in the Pedagogy courses, the rookie students, the student-teachers that are beginners and student-teachers that do have experience. We have observed that plenty of the students from the Pedagogy course are living the experience of being a student and being a teacher at the same time, but some of these students already have been teachers and are returning to the classrooms as students of a course that proposes "the graduation for being a teacher". Believing that a part of the teacher profession's learning only occurs or begins with the exercise, and that the professional exercise is the condition to consolidate the process of becoming a teacher, we question what are the relations between the learning and the teach exercise and how these relations are consolidated. This thesis is an exercise of constructing an intertext, that assembles other voices and dialogs with theories and researches that attribute to the language a central aspect in the formation of the thought and in the attribution of sense and signification of the world and its things. We weave a dialog with the propositions of Jerome Bruner, Paulo Freire, Antonio Nóvoa and also with the researches that use the (self) biographic approaching. These dialogs are the background of this study, a proposition to comprehend the student-teachers as subjects that are constituted in the field of the intersubjectivity, retrieving elements of its formation routes and having, as aims of this study: the analysis of the teacher education from the point of the student-teachers narratives, the investigation of the teacher-student simultaneous processes, and the elaboration of a profile of the students of the Pedagogy course that live, at the same time, the condition of teacher and student, interpretating, with the use of the criticizing hermeneutic, the meaning of the docent practices inside of the graduation processes.